ANALISIS ʿURF TERHADAP TRADISI MAPPATIKKA: STUDI KASUS DI DESA SONGING KABUPATEN SINJAI SULAWESI SELATAN - Zulkifli, Zulkifli; Kurniati, Kurniati; Musyfika Ilyas (Bajang Institute, 2025)
This study analyzes the Mappatikka tradition, a ritual practiced by the people of Songing Village, South Sulawesi, to restrain, delay, or divert rain, through an Islamic legal approach based on the concept of ʿurf. The main issue of this study stems from the debate regarding the boundaries between local traditions and religious practices in Muslim communities, particularly regarding accusations of syncretism in traditional rituals. This study aims to assess the position of Mappatikka as a cultural practice within the context of Islamic law and to understand the community's perception of the spiritual and social significance of the tradition. Using a qualitative-descriptive approach, this study combines textual analysis of classical and contemporary Islamic literature with field observations to uncover the construction of meanings and values ​​that exist within the community. The results show that Mappatikka is not viewed as a practice that contradicts the creed, but rather as a form of collective prayer and social endeavor that embodies the values ​​of faith, solidarity, and ecological responsibility. Based on the ʿurf analysis, this tradition is categorized as ʿurf ṣaḥīḥ because it does not conflict with the principles of monotheism and provides social and cultural benefits for the local community. This finding confirms that ʿurf can function as a contextual analysis instrument in understanding culture-based religious practices, and shows that the integration between custom and sharia is a form of dynamic adaptation that enriches the treasury of Nusantara Islam